Lactic Acid Bacteria (Lactobacillus bulgaricus and Streptococcus thermophillus) in Yogurt Inhibit the Growth of Escherichia coli, Salmonella typhimurium, and Shigella sp. In Vitro - Peramiarti, IDSAP (Jurnal Kedokteran Brawijaya, 2021)
Diarrhea is defecation with a frequency more often than usual (three times or more) a day (10 mL/kg/day) with a soft or liquid consistency, even in the form of water alone. Pathogenic bacteria, such as Escherichia coli, Salmonella typhimurium, and Shigella sp., play a role in many cases, to which antibiotics are prescribed as the first-line therapy. However, since antibiotic resistance cases are often found, preventive therapies are needed, such as consuming yogurt, which is produced through a fermentation process by lactic acid bacteria (LAB). This research aimed to determine the activity of lactic acid bacteria (Liactobacillus bulgaricus and Streptococcus thermophilus) in yogurt in inhibiting the growth of the pathogenic bacteria E. coli, S. typhimurium, and Shigella sp. The research applied in vitro with the liquid dilution test method and the true experimental design research method with post-test-only and control group design. The design was used to see the inhibitory effect of yogurt LAB on the growth of E. coli, S. typhimurium, and Shigell sp. to compare the effect of several different yogurt concentrations, namely 20%, 40%, 60%, and 80%. The results of the Least Significance Different analysis showed that there was a significant difference between yogurt with a concentration of 0% and that with various concentrations in inhibiting the growth of E. coli, S. typhimurium, and Shigella sp. with a p-value of <0.05. Whereas, there was no significant difference in the various concentrations of yogurt in inhibiting the growth of the three kinds of bacteria with a p-value of > 0.05.Â